Description of two new Chinese Parvispinia and new collection data for P. barkama (Lepidoptera, Noctuidae) - Chen, Enyong; Saldaitis, Aidas; Yakovlev, Roman V.; Volkova, Julia S.; Prozorov, Alexey M.; Zhou, Yonghong (Zootaxa, 2026)
Two new Chinese species of the genus Parvispinia Babics, Kononenko & Saldaitis, 2012 are described: P. clavata sp. nov. collected from Xizang, and P. dellabrunnai sp. nov. from Gansu. Both are compared with all other known species. Additionally, a second known collection locality in Xizang, 800 km west of the type locality in northern Sichuan, is reported for P. barkama Babics, Kononenko & Saldaitis, 2012; identification is confirmed by the genitalia of both sexes. All known collection localities for the Parvispinia species are mapped.